Ryan, Chris y Huang, Songsham (eds.) (2013). Tourism in China: Destinations, Planning and Experiences - Aureli Lojo Blesa (Documents d'Anàlisi Geogràfica, 2015)
Ryan, Chris y Huang, Songsham (eds.) (2013) Tourism in China: Destinations, Planning and Experiences Bristol: Channel View Publications, 321 p. ISBN 978-1-84541-401-6